Municipal solid waste management with cost minimization and emission control objectives: A case study of Ankara - Mohsenizadeh, Melika; Tural, Mustafa Kemal; Kentel, Elçin (Sustainable cities and society, 2020)
•Network design for municipal solid waste management (MSWM) systems is considered.•Impact of vehicular emissions on locational planning of MSWM systems is investigated.•A bi-objective (cost & emission) facility location problem is solved by an MILP model.•Proposed model is applied to the MSWM system of Ankara to locate transfer stations.•Impact of speed variations on both objectives is investigated by simulation analyses. Proper management of municipal solid waste (MSW) has been a crucial aspect of every society due to its social, environmental, and economic impacts. Operations research techniques have frequently focused on cost minimization objectives in locational planning of municipal solid waste management (MSWM) systems. However, transportation constitutes an integral part of this system producing a considerable amount of greenhouse gas (GHG) emissions. Therefore, sustainable management of this system with GHG emissions minimization considerations is necessary to preserve the resources and protect the environment. In this study, a bi-objective optimization model is proposed to minimize system cost and carbon dioxide (CO2) emission resulting from transportation activities in locational planning of MSWM systems. The proposed model is applied to MSWM system of Ankara to introduce transfer stations (TSs). Two extensions of the current system are examined, namely, the extended and hybrid systems, where MSW is only transported through TSs in the former, while direct shipments are also allowed in the latter. For both extensions, it is observed that with no or little increase in cost, considerable savings in emission can be achieved. Simulation analyses show that CO2 emission and cost are not subject to a considerable change due to speed variations of vehicles.